The exploration of Form, Pattern, Character on Settlement and Traditional Houses of Bali Aga Village, Case Study: Pedawa Village, Banjar District, Buleleng Regency, Bali. - Prajnawrdhi, Tri Anggraini (Journal of Civil Engineering, Architecture and Built Environment; Vol 1 No 1 (2017): Civil Engineering, Architecture and Built Environment, 2020)
esearch on Bali Aga Village (Indigenous Village in Bali) has become one fundamental issue in architecture in Bali today. This paper unveiled all information in regards to the form, pattern and character of the settlement and the traditional housing at Pedawa Village with its uniqueness characteristic and has not been explored yet. The strength of tradition, culture and local belief are the reflected into their daily life; and has become the spirit of pattern, form and character of the village and traditional houses. Hence, this spirit is the foundation of the village conservation. The concept of Tri Hita Karana is the concept of harmonious relationships between human with the God and the Nature has become the main foundation of the concept of the traditional house and village pattern. This concepts influence the natural village linier pattern with the mountain as sacred orientation and the sea as the profane orientation. Case study method applied for this research. Both primary and secondary data from interview, site observation and literature data analyzed with qualitative analysis. The result shows that the exploration of the shape, pattern and character of the settlement and traditional houses in Pedawa village generate the few strategies to conserve this village which could also be used to conserve the other Bali Aga village s in Bali. Keywords:  Bali Aga, culture, Pedawa Village, traditional house